Mortality Test Of Spice Plants As Biolarvicides Against Aedes Aegypti Larvae: Literature Review - Syaka, Muthiiah Khodista; Kurniawan, Betta; Saftarina, Fitria (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Dengue hemorrhagic fever (DHF) remains a global public health issue, transmitted through the bite of the Aedes aegypti mosquito. One method of disease prevention is the use of insecticides in the form of larvicides. Chemical larvicides have long been used but carry the risk of inducing resistance; therefore, research into the development of alternative larvicides is necessary. Indonesia’s rich biodiversity of spices presents a promising opportunity for the development of spice-based biolarvicides. This study was conducted in the form of a literature review, aiming to provide an overview of mortality tests of spice plants as biolarvicides against Aedes aegypti larvae. The findings from the reviewed literature indicate that two spices—tobacco leaves (Nicotiana tabacum) and zodia leaves (Evodia suaveolens)—in ethanol extract form achieved 100% larval mortality at all tested concentrations. The review also identified a variety of other spices with potential as biolarvicides based on larvicidal tests, with 9 out of 20 spices exhibiting 100% larval mortality rates in the summarized studies. It can thus be concluded that various spice plants demonstrate significant mortality test results and hold potential as alternative biolarvicides against Aedes aegypti larvae. Continued efforts to conduct standardization tests on these spice plants are necessary to develop them into standardized biolarvicidal agents.